Answer:
Combine like terms onto one side of the equation
Step-by-step explanation:
You have
-x^2 -4x - 3 = 2x + 5
It seems that we should combine like terms to make this equations smaller.
-x^2 - 4x - 3 - 2x - 5 = 0
-x^2 -6x - 8 = 0
- (x + 2)(x + 4) = 0
x = -2 or x = -4
Hello!
(4y + 8) - (7y - 12) = 11 is 1(4y + 8) - 1(7y - 12) = 11
1(4y + 8) - 1(7y - 12) = 11 Given
4y + 8 - 7y + 12 = 11 Distribute the 1 and the -1
-3y + 20 = 11 Combine like terms
-3y = -9 Subtract 20 from both sides
y = 3 Divide both sides by -3
Answer:
y = 3
Answer:
m=49/4
Step-by-step explanation: